Facile Solvothermal Synthesis of BiOCl/ZnO Heterostructures with Enhanced Photocatalytic Activity. (18th December 2014) - Li, Yong-Fang; Zhang, Ming; Guo, Dan-Lu; He, Fei-Xia; Li, Ying-Zhu; Wang, Ai-Jun
Abstract : Well-defined nanosheet-assembled (BiOCl) x (ZnO)1− x nanoflowers were synthesized by a solvothermal method. It was found that ZnO nanoparticles were anchored on the flower-like BiOCl nanostructures, as demonstrated by varying the initial compositions of the Bi precursor and the volume ratios of mixed solvents (ethylene glycol to water). The as-prepared (BiOCl)0.6 (ZnO)0.4 nanocomposites showed enhanced photocatalytic activity toward rhodamine B degradation under ultraviolet (UV) irradiation. And the photocatalytic mechanism was discussed in detail.